Dagli archivi il Progetto per un Albergo-Rifugio tipo in Valmalenco di Gianni Albricci e Marco Zanuso (1938) - Eugenio Lux (ArchAlp)
Winner of the 1938 Littoriali della Cultura e dell’Arte, the project for a Hotel-Refuge in Valmalenco (2000 m altitude) by Gianni Albricci (1916-2001) and Marco Zanuso (1916-2001) was conceived by two young students from the Faculty of Architecture at the Politecnico di Milano. The skillful design combines traditional alpine materials with innovative solutions, reflecting the autarkic policies of the Fascist era. Albricci and Zanuso’s proposal, selected for its clear spatial organisation and thoughtful response to the mountain context, included a hundred guest beds, a dining area, and recreational spaces designed to optimise natural light and comfort for climbers. Rediscovered in the Historical Archives of the Politecnico di Milano through the research of Federico Bucci (1959-2023), the project exemplifies the integration of functional requirements and modernist principles, lauded at the time by Giuseppe Pagano (1896-1945) in “Casabella”. Although never built, the design remains a significant example of high-altitude architecture and the intersections between politics, culture, and design in 1930s Italy. The original drawings are now on display at the Made in Polimi exhibition, celebrating the legacy of architectural education and experimentation at the Politecnico di Milano.